EXPLORING FIFTH-GRADE STUDENTS’ INTRINSIC MOTIVATION IN SCIENCE LEARNING: A QUALITATIVE CASE STUDY AT GMIT KUANINO 1 ELEMENTARY SCHOOL, KUPANG, INDONESIA - Sesilia H. Kein; Femberianus.S. Tanggur; Cornelia A. Naitili (Universitas Citra Bangsa, 2026)
Intrinsic motivation plays a critical role in sustaining students’ engagement and persistence in science learning, particularly at the primary level. This study explores (1) how intrinsic learning motivation is manifested among fifth-grade students in science lessons and (2) what teacher and school efforts support the development of such motivation at GMIT Kuanino 1 Elementary School, Kupang City, Indonesia. A descriptive qualitative approach was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis, enabling triangulation of information across sources. Findings indicate that students’ intrinsic motivation is supported by multiple interacting factors: (a) teachers’ use of varied and appropriate instructional methods, (b) utilization of learning media, (c) optimization of available facilities and learning resources, (d) continuous improvement of teacher quality through school programs, and (e) the creation of a pleasant and encouraging classroom climate. In addition, students’ enthusiasm for learning and the availability of basic classroom resources (e.g., tables, chairs, whiteboards, textbooks) strengthened participation in science learning activities. These results suggest that intrinsic motivation in primary science learning can be fostered through coherent pedagogical practices and supportive school environments. Implications are discussed for classroom instruction and school-level support to enhance student engagement in science learning.